Structural and adaptive features of the vegetative organs of Lophanthus anisatus Benth. in the conditions of the introduction of Uzbekistan - G.M. Duschanova; D.K. Fakhriddinova; S.Kh. Abdinazarov; N.K. Aliyeva (Caspian Journal of Environmental Sciences)
In this study, we examined the morphoanatomical structure of the vegetative organs of Lophanthus anisatus, common in the conditions of introduction, the features of structural adaptation and localization of biologically active substances, i.e. pharmacological activity. Based on the study of the anatomical structure of assimilative and axial organs under the conditions of introduction (Tashkent and Jizzakh) of L. anisatus, species-specific diagnostic features were determined. According to a comparative analysis of the anatomical features of the vegetative organs, it was established that under the conditions of the introduction of the Tashkent Botanical Garden, mesomorphic signs predominate in the assimilation and axial organs, and in the conditions of the Jizzakh region - xeromorphic ones. The localization of biologically active substances in the assimilating and storage tissues of the main tissue was also determined. These identified diagnostic characters are considered permanent taxonomic characters and are used in taxonomy and in the process of identifying the raw material of the species.